Mapeamento geoquímico por sedimentos de corrente na borda do Cráton São Francisco e Cinturão Brasília, Minas Gerais: definição de background geoquímico e aplicação de análise estatística multivariada. - Rafael Tarantino Amarante (2021)
The environmental impact over river environments has increased public attention due to tragedies related to the collapse of dams within basins of Doce and Paraopebas rivers, which caused dispersion of potentially toxic elements along the watercourses, therefore the need to apply tools that enable qualitative regional monitoring of water resources is necessary as a public policy of sustainability and quantification of the impact on human activities. However, the environmental quality analysis that addresses anomalous chemical concentrations in sediments, has as a limiting factor on defining of which values are considered natural and which can be defined as potentially influenced by anthropic activity. Therefore, the use of geochemical background definition methodologies combined with geochemical mapping through uni, bi and multivariate statistical analyzes allow the cartographic regionalization of geochemical data to represent the spatial relationship of the chemical dispersion structure, as well as to define the likely lithological sources and possible anthropogenic influences over stream sediments. The purpose of this project is to define natural background values, according to different methodologies, allied to geochemical mapping techniques to understand which element concentrations are naturally anomalous and which can be considered influenced by anthropogenic activities over sediments of Médio São Francisco and Alto Paranaíba watersheds, within the Zinciferous District of Vazante, on the border of the São Francisco Craton with the Brasília Belt, in Minas Gerais. The analyses were applied to obtain the chemical concentration data from the sediment sampling survey of the Vazante-Paracatu project, conceived by the Geological Survey of Brazil - CPRM, in 2017. The sediment were collected by composite sampling in an active current channel, in the laboratory they were dried at 60 ºC in ovens, quartered and sieved in meshes with an opening size of <80 mesh (<0.175 mm), then submitted to digestion with acqua regia and analyzed in ICPOES (Inductively Coupled Plasma Optical Emission Spectroscopy) to obtain the major elements and ICP-MS (Inductively Coupled Plasma Mass Spectrometry) for the minor and trace elements concentrations, totaling 53 elements. The geochemical background was calculated from several methods widely used on research, namely: median + 2x MAD, TIF and based on percentiles. Univariate statistics were applied by generating statistical summaries, boxplots and normality tests to assess the distribution of chemical elements. While the bivariate analysis, based on correlation matrix between the elements, can provide the main geochemical associations that were used as a prerequisite for the Factor Analysis application, that was performed using the method of extraction of the main factors, with previous data transformation by the CLR logratio.As a result of the natural background values determination, it was calculated by main lithological units, which makes it possible to assess the natural enrichment of certain elements present in these rocks, as well allowing the definition of natural concentration thresholds according to the regional context of the study area. Univariate statistics allowed the spatialization and identification of anomalies for Fe (>14.59%), Al (>7.37%), Mg (>0.82%), P (>1567 mg/kg), Zn (> 206 mg/kg), Pb, Cd (>0.47 mg/kg), Cu (>89 mg/kg), Ni (>94.90 mg/kg), Cr (> 170 mg/kg), As ( >38 mg/kg), Ba (>295 mg/kg), Co (>155.10 mg/kg), LREE (>312.00 mg/kg), Th (>21.01 mg/kg), U (>3.25 mg/kg), V (214 mg/kg). The most representative correlations (> 0.80) are between the elements Al and Ga; Co and Mn; Co and Ni; Cr and V; Cu and Ni; Ga and Sc. The factor analysis resulted in 6 main factors that represent the 8 main geochemical associations in the study area, they are: (1) Co, Mg, Ni and Zn; (2) Al, Cs, Ga, Sn and V; (3) Cr, Ni and V; (4) Cs, K and Rb; (5) As and Fe; (6) Cd, Pb and Zn; (7) LREE, Th and U; (8) Ba, P and Sr. As practical implications, the geochemical database, with the definition of naturally available concentration values, allows mineral and agricultural activities in the region to quantify and monitor the environmental impact of their resulting production chain that affects the dispersion of potentially toxic elements within the river sediments of two main hydrographic watershed under intense anthropic activity.